Menelisik Ideologi Persatuan Kitab Arba’in Karya KH. Hasyim Asy’ari: : Sebuah Analisis Wacana Kritis - Alfin Hidayatullah; Ahmad Misbakhul Amin; Muhammad Fadhil Febryansyah; Syaiful Rijal; Ahmat Saepuloh (Prodi Ilmu Hadis Fakultas Ushuluddin dan Dakwah Universitas Islam Negeri Madura, 2025)
The rise of Islamic radicalism in post-reform Indonesia poses a serious challenge to national integration and religious harmony. Doctrines and movements grounded in exclusivism and intolerance toward religious diversity often trigger societal fragmentation. In this context, KH. Hasyim Asy'ariâ€”founder of Nahdlatul Ulamaâ€”formulated an ideological response rooted in his compilation of á¸¥adÄ«ths entitled Arbaâ€˜Ä«na á¸¤adÄ«than Tataâ€˜allaqu Bi MabÄdiâ€™ Jamâ€˜iyyah Nahdlatil Ulamaâ€™. This study aims to examine the values of unity expressed through three core á¸¥adÄ«ths thematically linked to the concept of social cohesion, namely á¸¥adÄ«th no. 16, 22, and 39. Employing a qualitative-descriptive method, the research adopts Teun A. van Dijkâ€™s Critical Discourse Analysis framework, which incorporates macro-structure, schematic form, semantics, syntax, stylistics, rhetorical strategy, and social cognition. The findings reveal that while the isnÄd (chain of transmission) of the three á¸¥adÄ«ths variesâ€”ranging from á¸¥asan li dhÄtihi, á¹£aá¸¥Ä«á¸¥ li dhÄtihi, to á¸aâ€˜Ä«fâ€”their matn (textual content) is evaluated as á¹£aá¸¥Ä«á¸¥ based on compatibility with reason and foundational Islamic principles. The thematic values identified include empathy, solidarity, tolerance of difference, and the imperative to preserve communal harmony. This compilation of á¸¥adÄ«ths functions not merely as a religious text but also as an ideological manifesto responding to the socio-religious challenges of its time. In conclusion, Arbaâ€˜Ä«na á¸¤adÄ«than reflects a traditionalist yet progressive vision of Islam rooted in Ahl al-Sunnah wa al-JamÄâ€˜ah, offering a normative framework for promoting moderation, pluralism, and national unity in contemporary Muslim societies.